Simulation of Physical and Mechanical Properties to Increase the Strength of the Cutting Ceramics - A. Moskvitin, Alexey; A. Gorovenko, Lyubov; V. Kovriga, Evgenia; A. Sumskaya, Olga; S. Abelyan, Akop (International Journal of Engineering and Technology, 2018)
According to studies [1], cutting tools with plates made of cutting ceramics alloyed with carbide-forming elements have higher heat resistance than standard plates made of cutting ceramics in the delivery stage, since their properties do not meet the requirements. Cutting ceramics with the addition of a nickel alloying element to its main standard fraction has a low heat resistance. With the addition of the manganese alloying element, heat resistance and corrosion resistance and wear resistance of cutting tools equipped with cutting ceramics are reduced. The main alloying element is chromium, which, depending on its quantity, indicates increased or high heat resistance in cutting ceramics.Â Â